2020
DOI: 10.1021/acsestwater.0c00155
|View full text |Cite
|
Sign up to set email alerts
|

Pilot UV-AOP Comparison of UV/Hydrogen Peroxide, UV/Free Chlorine, and UV/Monochloramine for the Removal of N-Nitrosodimethylamine (NDMA) and NDMA Precursors

Abstract: Three different ultraviolet-advanced oxidation processes (UV-AOPs) (UV/hydrogen peroxide, UV/free chlorine, and UV/supplemental monochloramine) used in full advanced treatment (FAT) for potable reuse were evaluated at pilot scale using reverse osmosis (RO) permeate from a FAT facility. Oxidant concentrations were varied, and each AOP was assessed for its ability to remove N-nitrosodimethylamine (NDMA) and NDMA precursors. For all AOPs, NDMA was removed well (to near 1.2 ng/L). However, UV/free chlorine exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…While our results indicated that net NDMA formation associated with the UV/NH 2 Cl/Cl-DMA pathway is unlikely to be important at 700 mJ/cm 2 , net NDMA formation was important at lower fluence (Figure ). Moreover, recent pilot tests applying 700–1300 mJ/cm 2 at two potable reuse facilities , have indicated that effluent NDMA concentrations are more difficult to control by the UV/HOCl AOP than by the UV/H 2 O 2 AOP. Our results demonstrate that this challenge occurs because chlorine addition promotes NDMA formation by dark breakpoint chlorination reactions over a <10 min time interval.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While our results indicated that net NDMA formation associated with the UV/NH 2 Cl/Cl-DMA pathway is unlikely to be important at 700 mJ/cm 2 , net NDMA formation was important at lower fluence (Figure ). Moreover, recent pilot tests applying 700–1300 mJ/cm 2 at two potable reuse facilities , have indicated that effluent NDMA concentrations are more difficult to control by the UV/HOCl AOP than by the UV/H 2 O 2 AOP. Our results demonstrate that this challenge occurs because chlorine addition promotes NDMA formation by dark breakpoint chlorination reactions over a <10 min time interval.…”
Section: Resultsmentioning
confidence: 99%
“…30 Pilot-scale comparisons of UV/H 2 O 2 and UV/HOCl AOPs conducted within FAT trains at the Donald C. Tillman facility in Los Angeles (CA) and at the Orange County Water District (CA) demonstrated that both AOPs reduced NDMA concentrations, but that effluent NDMA concentrations were higher for the UV/HOCl AOP. 27,28 Because direct UV photolysis of NDMA should be similar between these AOPs, these observations suggested that NDMA was forming concurrently during UV/HOCl AOP treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The UV/chlorine process is an emerging advanced oxidation process (AOP) for oxidation and disinfection in water treatment. UV photolysis of free chlorine leads to the generation of hydroxyl radicals (HO • ) and reactive chlorine species (RCS), such as Cl • , Cl 2 •– , and ClO • , which are effective for the abatement of refractory micropollutants and inactivation of pathogens. However, the formation of disinfection byproducts (DBPs) is a major concern. , Compared to chlorination alone, more chlorinated products have been identified during UV/chlorine treatment of natural organic matter (NOM). , Meanwhile, UV/chlorine treatment can lead to increased formation of DBPs, especially nitrogenous DBPs (N-DBPs) with high toxic potency. Nevertheless, the enhanced formation of many N-DBPs during UV/chlorine treatment is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%